Understanding the buckling behaviour of steered tows in automated dry fibre placement (ADFP) - Matveev, Mikhail Y.; Schubel, Peter J.; Long, Andrew C.; Jones, I.A. (Elsevier, 2016)
Technologies for automated fibre lay-up have proven their usefulness in composites manufacturing. Further development of the technologies, such as Automated Dry Fibre Placement (ADFP), allow further reduction of waste and increase of the design space through tow steering which enables creation of composites with tailored properties. Tow steering is, however, limited by possible defects such as wrinkles which result from mismatch of fibre length and steering path. This paper addresses wrinkle formation at different steering radii and provides a closed-form solution for the problem. Experimental results are used for estimation of the model parameters and validation of the model. An analytical framework is used to explore effects of processing parameters on defect formation. It was found that the tack stiffness has the greatest influence on defect formation. Parametric studies showed that increase of the temperature within the admissible temperature window can improve the tack properties and hence improve the lay-up.